Analyzing Trigonometry Learning Gaps A Systematic Review of Error Patterns Among Indonesian Students - Hakim, Rahman Nul (Tirtamath: Jurnal Penelitian dan Pengajaran Matematika, 2025)
Trigonometry continues to pose a significantchallenge for Indonesian learners, with recurring mistakesimpeding their academic development. This comprehensiveliterature review explores the various types of error patterns intrigonometry and examines the educational factors that contributeto these challenges. Utilizing the PRISMA framework, wereviewed six pertinent studies from an initial selection of 279publications. The results classify errors into four primarycategories: comprehension errors (misinterpreting problems),transformation errors (selecting incorrect formulas), process skillerrors (mistakes in calculations), and encoding errors (issues withpresenting final answers). These errors were linked to severaleducational factors, including deficiencies in foundationalknowledge, an overreliance on memorization, insufficientproblem-solving instruction, and assessment approaches thatprioritize outcomes rather than the processes involved. Theresearch underscores the necessity for pedagogical changes thatprioritize conceptual understanding, real-world applications, andthe development of metacognitive skills. These findings offerimportant recommendations for educators and policymakers whoaim to enhance trigonometry teaching in Indonesia andcomparable educational settings